Back Propagation and Transformation Methods in Artificial Intelligence Systems (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Detailed description of methods of back propagation and back transformation also distributions for training of neural networks is given. A comparative estimation of a priority of methods of back transformation and back propagation for the decision of tasks of synthesis and training of neural networks, also for intelligent automatic measuring and AI systems for the first time is carried out.